World Health Organization global air quality guideline recommendations: Executive summary. Issue 7 (8th February 2022) - Goshua, Anna; Akdis, Cezmi A.; Nadeau, Kari C.
Abstract: Air pollution is a leading cause of death globally and has resulted in the loss of millions of healthy years of life. Moreover, the health burden has fallen disproportionately upon people in many low‐ and middle‐income countries, where air quality continues to deteriorate. To assist authorities and civil society in improving air quality, World Health Organization has published the first global update to its 2005 air quality guidelines based on a significantly improved body of evidence. To facilitate the implementation of the World Health Organization Global Air Quality Guideline recommendations, this article summarizes the purpose and rationale of the quantitative air quality guidelines and interim target levels for six key pollutants: particulate matter 2.5, particulate matter 10, sulfur dioxide, nitrogen dioxide, ozone, and carbon monoxide. In addition, good practice statements are established for the management of pollutants of concern that lack sufficient evidence to substantiate numerical targets. Abstract :